2020
DOI: 10.1093/ajcn/nqaa104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lean red meat combined with a multicomponent exercise program on muscle and cognitive function in older adults: a 6-month randomized controlled trial

Abstract: ABSTRACT Background Exercise and increased dietary protein have been linked to improved muscle and cognitive health, but the combination may be more effective. Objective In this study performed in community-dwelling older adults undergoing a 3-d/wk resistance-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…Notably, when a similar proteinenriched diet intervention using 2 × 80 g of cooked red meat 6 days per week was combined with thrice-weekly resistance exercise training for 16 weeks, leg extension strength increased by 28% in the meat plus exercise group as compared to 10% in the exercise only group (Daly et al, 2014). However, when the study was repeated with additional protein only on training days, no differences between groups was observed (Formica et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Notably, when a similar proteinenriched diet intervention using 2 × 80 g of cooked red meat 6 days per week was combined with thrice-weekly resistance exercise training for 16 weeks, leg extension strength increased by 28% in the meat plus exercise group as compared to 10% in the exercise only group (Daly et al, 2014). However, when the study was repeated with additional protein only on training days, no differences between groups was observed (Formica et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Multiple studies have examined the effects of beef intake on skeletal muscle-based outcomes in older adults [58,59,[214][215][216]. Recent reviews have concluded that beef and/or the nutrients found within beef may improve muscle function [214,217].…”
Section: Animal Food Sourcesmentioning
confidence: 99%
“…Lean red meat enhanced the effects of resistance training on muscle mass and strength in older females [59] and in 1 repetition maximum leg extension strength in older males [215]. In contrast, when examining the effects of lean beef in addition to resistance training, no additional benefits were observed in older adults when beef was consumed twice a week for 24 weeks [216]. Additionally, lean beef and protein supplementation had no positive effect on fat-free mass in older adults [215,218].…”
Section: Animal Food Sourcesmentioning
confidence: 99%
“…In one study, provision of daily milk protein, in combination with resistance training, for 24 weeks was shown to improve information processing speed among frail elderly adults while the non-supplemented group improved in attention and working memory ( 54 ). More recently, 24 weeks of habitual resistance and endurance exercise, based on a 10-point rating of perceived exertion intensity prescription, and lean red meat supplementation yielded similar increases in global cognition and executive function when compared to a control group ( 55 ). It should be noted, however, that this study was conducted against a dietary backdrop where all groups were consuming >1.2 g·kg −1 ·d −1 ( 55 ).…”
Section: Aging Strong: Mental Strength To Support Life-long Healthmentioning
confidence: 99%
“…More recently, 24 weeks of habitual resistance and endurance exercise, based on a 10-point rating of perceived exertion intensity prescription, and lean red meat supplementation yielded similar increases in global cognition and executive function when compared to a control group ( 55 ). It should be noted, however, that this study was conducted against a dietary backdrop where all groups were consuming >1.2 g·kg −1 ·d −1 ( 55 ). Thus, the impact of a low(er) protein diet (e.g., 0.8 g·kg −1 ·d −1 ) on cognitive outcomes cannot be deciphered.…”
Section: Aging Strong: Mental Strength To Support Life-long Healthmentioning
confidence: 99%